How Language Shapes Word of Mouth's Impact - Packard, Grant; Berger, Jonah (Journal of Marketing Research, 2017)
Word of mouth affects consumer behavior, but how does the language used in word of mouth shape that impact? Might certain types of consumers be more likely to use certain types of language, affecting whose words have more influence? Five studies, including textual analysis of more than 1,000 online reviews, demonstrate that compared to more implicit endorsements (e.g., “I liked it,” “I enjoyed it”), explicit endorsements (e.g., “I recommend it”) are more persuasive and increase purchase intent. This occurs because explicit endorsers are perceived to like the product more and have more expertise. Looking at the endorsement language consumers actually use, however, shows that while consumer knowledge does affect endorsement style, its effect actually works in the opposite direction. Because novices are less aware that others have heterogeneous product preferences, they are more likely to use explicit endorsements. Consequently, the endorsement styles novices and experts tend to use may lead to greater persuasion by novices. These findings highlight the important role that language, and endorsement styles in particular, plays in shaping the effects of word of mouth.